Los apoyos audiovisuales y el Pensamiento Histórico: una propuesta metodológica para su aplicación en el aula - Nicolás Mauricio Calderón Pantoja; Carlos de la Rosa Gómez (Clio y Asociados)
The aim of this work is to systematize a model that considers the use of audiovisual resources as a complement to the development of Historical Thinking in the classroom. For the theoretical basis, we reviewed postulates about Historical Thinking in relation to film materials. We examined references regarding the relevance of complementing History classes with audiovisual material and structured criteria to help define selection parameters. For the construction of this model, we consulted dramaturgical texts through which we projected a guide serving as training for the teacher with tools to help them understand how to break down and analyze this material, and how to find the best way to use it in favor of the session and the construction of Historical Thinking. We conclude this work by providing projections in the pursuit of continuously improving didactic-pedagogical techniques that come to the aid of our students.